TREND DAN ESTIMASI PRODUKSI PADI DAN KONSUMSI BERAS DI PROVINSI KALIMANTAN TENGAH - Indah Pratiwi Gurning; Yuprin, A. D.; Eka Nor Taufik (Program Studi Agribisnis Jurusan Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Palangka Raya, 2019)
This study is conducted to determine the trend and estimation of rice production and rice consumption in Central Borneo Province. The study is held in Central Borneo Province by using secondary data from October 2017 to March 2018, using Least Square’s method. The results shows that the trend of rice production in Central Borneo Province in 2001-2015 is increasing. Same as paddy production which is increasing almost every year, rice production increasing almost every year. Estimation rice production in Central Borneo Province in 2016-2020 is also known that five years ahead, rice production will be increasing from year to year. Trend of rice consumption in Central Borneo Province in 2001-2015 is increasing every year, and Estimation of rice consumption in Central Borneo Province in 2016-2020 is known that five years ahead will be increasing from year to year although it can still be balanced with the value of production which is greater than consumption. Even the province of Central Borneo is also potential to surplus of rice till the year estimated 2020, that is 329.255,83 tons, so till 2020 rice production Central Borneo Province still can be sufficient for consumption need of the population.